Characterizations and analysis of the antioxidant, antimicrobial, and dye reduction ability of green synthesized silver nanoparticles - Riaz Muhammad (Green Processing and Synthesis, 2020)
The current study was conducted to assess the potential of ginger rhizome extract (Zingiber officinale) for the synthesis of silver nanoparticles (AgNPs) through the green method and its mitigating activity against pathogenic bacterial strains. AgNPs were synthesized through a simple one-step approach and characterized by UV-Visible (UV-Vis) spectroscopy, powder X-ray diffraction (PXRD), transmission electronic microscopy (TEM), and energy dispersive X-rays spectroscopy (EDS). PXRD and TEM results of AgNPs showed the face central cubic structures and predominantly spherical structures with a size of 6.5 nm. EDS analysis confirms the elemental silver in nanoparticles. Moreover, the impact of the pH, as well as temperature, during the synthesis of AgNPs has also been investigated. At 25°C and pH 5, there was no significant peak for AgNPs in the absorption spectra. However, with an increase in temperature from 25°C to 85°C and pH 5 to pH 11, particles started attaining the spherical shape of different sizes due to an increase in the reduction rate. The AgNPs displayed effective results against selected pathogenic strains, Pseudomonas aeruginosa (MTCC 424), Methicillin-resistant Staphylococcus aureus (ATCC 43300), and fungus Candida albicans (KACC 30003). The prepared AgNPs exhibited excellent antioxidant activity and catalytic reduction of methyl orange with the pseudo-first-order rate constant of 3.9 × 10−3.